Effect of Different Parameters on Intrinsic Uniformity Test For MEDISO Single-Head Gamma Camera - S. Zobly, Sulieman Moh.; Osman, Abdelbagi O. (Gezira Journal of Engineering and Applied Sciences, 2018)
The most basic and sensitive routine quality control (QC) of gamma camera is that of intrinsic uniformity. Intrinsic uniformity must be assessed daily and after each repair, it must be critically evaluated and any necessary action must be undertaken before using the gamma camera for patient imaging. The main objective of this work is to determine the best parameters for daily quality control testing of intrinsic uniformity for the single-head gamma camera from MEDISO Company installed at Institute of Nuclear Medicine - University of Gezira. Intrinsic uniformity test was done by placing a point source 99m TcO - ( 99m Tc) in front of the detector with removed collimator to measure the effect of correction matrix, source-to-camera distance, a count rate and activity volume on intrinsic uniformity. The results showed that the best intrinsic uniformity image obtained at distance of 100 cm, with correction matrix, activity volume in range of 0.1 - 0.4 ml in 3 ml syringe and count rate between 25 - 30 kcps which took less than 14 min to get uniform image.